Population effect of 10-valent pneumococcal conjugate vaccine on nasopharyngeal carriage of Streptococcus pneumoniae and non-typeable Haemophilus influenzae in Kilifi, Kenya: findings from cross-sectional carriage studies - Dr. Laura L Hammitt, MD; Donald O Akech, BSc; Susan C Morpeth, FRACP; Angela Karani, BSc; Norbert Kihuha, BSc; Sammy Nyongesa, MSc; Tahreni Bwanaali, MBA; Edward Mumbo, BSc; Tatu Kamau, MPH; Shahnaaz K Sharif, MD; Prof. J Anthony G Scott, FRCP (The Lancet Global Health, 2014)
Background: The effect of 7-valent pneumococcal conjugate vaccine (PCV) in developed countries was enhanced by indirect protection of unvaccinated individuals, mediated by reduced nasopharyngeal carriage of vaccine-serotype pneumococci. The potential indirect protection of 10-valent PCV (PCV10) in a developing country setting is unknown. We sought to estimate the effectiveness of introduction of PCV10 in Kenya against carriage of vaccine serotypes and its effect on other bacteria. Methods: PCV10 was introduced into the infant vaccination programme in Kenya in January, 2011, accompanied by a catch-up campaign in Kilifi County for children aged younger than 5 years. We did annual cross-sectional carriage studies among an age-stratified, random population sample in the 2 years before and 2 years after PCV10 introduction. A nasopharyngeal rayon swab specimen was collected from each participant and was processed in accordance with WHO recommendations. Prevalence ratios of carriage before and after introduction of PCV10 were calculated by log-binomial regression. Findings: About 500 individuals were enrolled each year (total n=2031). Among children younger than 5 years, the baseline (2009–10) carriage prevalence was 34% for vaccine-serotype Streptococcus pneumoniae, 41% for non-vaccine-serotype Streptococcus pneumoniae, and 54% for non-typeable Haemophilus influenzae. After PCV10 introduction (2011–12), these percentages were 13%, 57%, and 40%, respectively. Adjusted prevalence ratios were 0·36 (95% CI 0·26–0·51), 1·37 (1·13–1·65), and 0·62 (0·52–0·75), respectively. Among individuals aged 5 years or older, the adjusted prevalence ratios for vaccine-serotype and non-vaccine-serotype S pneumoniae carriage were 0·34 (95% CI 0·18–0·62) and 1·13 (0·92–1·38), respectively. There was no change in prevalence ratio for Staphylococcus aureus (adjusted prevalence ratio for those <5 years old 1·02, 95% CI 0·52–1·99, and for those ≥5 years old 0·90, 0·60–1·35). Interpretation: After programmatic use of PCV10 in Kilifi, carriage of vaccine serotypes was reduced by two-thirds both in children younger than 5 years and in older individuals. These findings suggest that PCV10 introduction in Africa will have substantial indirect effects on invasive pneumococcal disease. Funding: GAVI Alliance and Wellcome Trust.